Once a liar - Brady, A. F. (London : HQ, 2019)
Manhattan defense attorney Peter Caine is accused of the murder of his former lover, Charlie Doyle, the daughter of the Manhattan DA.
Keywords: Murder -- Investigation -- Fiction; Criminal defense lawyers -- Fiction; Psychological fiction; Detective and mystery fiction; Fiction; Psychological fiction; Thrillers (Fiction); Suspense fiction; Legal stories; Psychological fiction; Thrillers (Fiction)